Geographic variation in responses of kelp forest communities of the California Current to recent climatic changes. (9th September 2020) - Beas‐Luna, Rodrigo; Micheli, Fiorenza; Woodson, C. Brock; Carr, Mark; Malone, Dan; Torre, Jorge; Boch, Charles; Caselle, Jennifer E.; Edwards, Matt; Freiwald, Jan; Hamilton, Scott L.; Hernandez, Arturo; et al.
Abstract: The changing global climate is having profound effects on coastal marine ecosystems around the world. Structure, functioning, and resilience, however, can vary geographically, depending on species composition, local oceanographic forcing, and other pressures from human activities and use. Understanding ecological responses to environmental change and predicting changes in the structure and functioning of whole ecosystems require large‐scale, long‐term studies, yet most studies trade spatial extent for temporal duration. We address this shortfall by integrating multiple long‐term kelp forest monitoring datasets to evaluate biogeographic patterns and rates of change of key functional groups (FG) along the west coast of North America. Analysis of data from 469 sites spanning Alaska, USA, to Baja California, Mexico, and 373 species (assigned to 18 FG) reveals regional variation in responses to both long‐term (2006–2016) change and a recent marine heatwave (2014–2016) associated with two atmospheric and oceanographic anomalies, the "Blob" and extreme El Niño Southern Oscillation (ENSO). Canopy‐forming kelps appeared most sensitive to warming throughout their range. Other FGs varied in their responses among trophic levels, ecoregions, and in their sensitivity to heatwaves. Changes in community structure were most evident within the southern and northern California ecoregions, while communities in the center of the range were more resilient. We report a poleward shift in abundance of some key FGs. These results reveal major, ongoing region‐wide changes in productive coastal marine ecosystems in response to large‐scale climate variability, and the potential loss of foundation species. In particular, our results suggest that coastal communities that are dependent on kelp forests will be more impacted in the southern portion of the California Current region, highlighting the urgency of implementing adaptive strategies to sustain livelihoods and ensure food security. The results also highlight the value of multiregional integration and coordination of monitoring programs for improving our understanding of marine ecosystems, with the goal of informing policy and resource management in the future. Abstract : We evaluated how kelp forest ecosystem key functional groups responded to long‐term environmental change. We integrated a large scale, long term data set from monitoring programs spanning the large marine ecosystems of the California Current. Results revealed changes in community structure were most evident within the southern and north‐central ecoregions, and a poleward shift in abundance of habitat‐forming groups.